Micronucleus Assay in Exfoliated Buccal Epithelial Cells Using Liquid Based Cytology Preparations in Building Construction Workers - ARUL P; Shetty Smitha; Suresh Masilamani; Akshatha C (Iranian Society of Pathology, 2018)
Background and objective:Cytogenetic damage in exfoliated buccal epithelial cells due to environmental and occupational exposure is often monitored by micronucleus (MN) assay using liquid based cytology (LBC) preparations. This study was performed to evaluate MN in exfoliated buccal epithelial cells of building construction workers using LBC preparations. Material and methods: LBC preparations of exfoliated buccal epithelial cells from 100 subjects [50 building construction workers (cases) and 50 administrative staffs (controls)] was evaluated by May-Grunwald Giemsa, Hematoxylin and Eosin and Papanicolaou stains. Student's t test was used for statistical analysis and a P value of Results: The mean frequencies of MN for cases were significantly higher than controls regardless of staining methods used.There were statistically significant differences between smokers and non-smokers of the controls as well as duration of working exposure (5 years) and smokers and non-smokers of cases (P=0.001). However, there were meaningful differences regarding mean frequencies of MN between smokers, non-smokers, those with alcohol consumption or not in cases and controls using various stains (P=0.001). Conclusion: There was an increased risk of cytogenetic damage in building construction workers. However, evaluation of MN of exfoliated buccal epithelial cells in building construction workers serve as a minimally invasive biomarker for cytogenetic damage. LBC preparations can be applied for MN assay as it improves the quality of smears and cell morphology, decreases the confounding factors and reduces false positive results.